HDAC6 Inhibition Alleviates CLL-Induced T-Cell Dysfunction and Enhances Immune Checkpoint Blockade Efficacy in the Eμ-TCL1 Model - Maharaj, Kamira; Powers, John J.; Mediavilla-Varela, Melanie; Achille, Alex; Gamal, Wael; Quayle, Steven; Jones, Simon S.; Sahakian, Eva; Pinilla-Ibarz, Javier (Frontiers in Immunology, 2020)
Development of chronic lymphocytic leukemia (CLL) is associated with severe immune dysfunction. T-cell exhaustion, immune checkpoint upregulation, and increase of regulatory T cells contribute to an immunosuppressive tumor microenvironment. As a result, CLL patients are severely susceptible to infectious complications that increase morbidity and mortality. CLL B-cell survival is highly dependent upon interaction with the supportive tumor microenvironment. It has been postulated that the reversal of T-cell dysfunction in CLL may be beneficial to reduce tumor burden. Here, we report for the first time that selective histone deacetylase 6 (HDAC6) inhibition exerts beneficial immunomodulatory effects on CLL B cells and reverses immunosuppression of CLL T cells. In the euTCL1 murine model, genetic silencing or inhibition of HDAC6 reduced surface expression of programmed death-ligand 1 (PD-L1) on CLL B cells and lowered interleukin-10 (IL-10) levels. This occurred concurrently with a bolstered T-cell phenotype, demonstrated by alteration of coinhibitory molecules and activation status. Previous studies have highlighted roles for HDAC6 in regulation of immune cell phenotype and function. The data reported here suggest that CLL B cell phenotype may be altered by HDAC6-mediated hyperacetylation of the chaperone heat shock protein 90 (HSP90) and subsequent inhibition of the Janus kinase (JAK)/signal transducer and activator of transcription (STAT) pathway. Based on the beneficial immunomodulatory activity of HDAC6 inhibition, we rationalized that HDAC6 inhibitors could enhance immune checkpoint blockade in CLL. Conclusively, combination treatment with ACY738 augmented the antitumor efficacy of anti-PD-1 and anti-PD-L1 monoclonal antibodies in the euTCL1 model. These combinatorial antitumor effects coincided with an increased cytotoxic CD8+ T-cell phenotype. Taken together, these data highlight a role for HDAC inhibitors in combination with immunotherapy and provides the rationale to investigate HDAC6 inhibition together with immune checkpoint blockade for treatment of CLL patients.